Features of Control Processes in Organizational-Technical (Technological) Systems of Continuous Type - Korobiichuk, Igor; Ladanyuk, Anatoly; Boyko, Regina; Hrybkov, Serhii (My University, 2020)
Technological complexes of various industries are characterized by certain modes of operation (techno-logical regulations), which correspond to the set of vari-ables of different nature, which have a high-dynamics of change and determine the main technical and economic performance of the object. The aim of the research is to identify information software approaches to support decision-making in organizational-technical (techno-logical) systems. Research results are obtained through grouping, generalization and comparison methods. The scientific significance of the results are to determine the objective need to use intelligent decision support subsys-tems to quickly manage complex organizational-tech-nical systems based on both: clear and formalized data and knowledge and high-quality fuzzy estimates.
Keywords: sugar production; control object; technologi-cal monitoring; цукрове виробництво; об'єкт контролю; технологічний моніторинг; automated complexes; uncertainty of in-formation; neuro-fuzzy networks; автоматизований технологічний комплекс; невизначеність інформації; нейронечіткі мережі; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка